1992
DOI: 10.1111/j.1432-1033.1992.tb17162.x
|View full text |Cite
|
Sign up to set email alerts
|

A strong protein‐tyrosine kinase activity is associated with a baculovirus‐expressed chicken tkl gene

Abstract: We have previously described a gene named tkl (tyrosine kinase related to lck). It belongs to the src family of protein‐tyrosine kinases and among these it has significant homology to the lck gene (lymphoide cell kinase). The tkl gene product may represent the avian homolog of Lck, which is believed to participate in a lymphocyte‐specific signal transduction pathway by association with a membrane receptor. To study the biochemical properties of the protein, a nearly complete tkl gene (isolated from a cDNA libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(29 reference statements)
0
2
0
1
Order By: Relevance
“…Reiss et al (23) showed that GAPDH served as substrate for purified epidermal growth factor receptor kinase. It was also demonstrated by phosphoamino acid analysis that GAPDH was tyrosine phosphorylated by tyrosine kinase related to lymphode cell kinase (29). Likewise, Sergienko et al (24) found that rabbit muscle GAPDH contained phosphotyrosine.…”
Section: Discussionmentioning
confidence: 92%
“…Reiss et al (23) showed that GAPDH served as substrate for purified epidermal growth factor receptor kinase. It was also demonstrated by phosphoamino acid analysis that GAPDH was tyrosine phosphorylated by tyrosine kinase related to lymphode cell kinase (29). Likewise, Sergienko et al (24) found that rabbit muscle GAPDH contained phosphotyrosine.…”
Section: Discussionmentioning
confidence: 92%
“…Во-первых, модификация поверхностных остатков белковой молекулы, которая влияет на взаимодействие ГАФД с белкамипартнерами. Прежде всего, к этому типу относится фосфорилирование сериновых и тирозиновых остатков, приводящее к изменению связывания ГАФД с другими белками [12][13][14], а также гликирование лизиновых остатков, вызывающее инактивацию фермента и изменение некоторых его свойств [15,16]. Такой тип модификаций имеет важное значение для осуществления негликолитических функций ГАФД, из-за которых этот фермент получил поэтичное название «Moonlighting protein», не очень красиво переведенное на русский язык как «белок подработки» [17].…”
Section: пост-трансляционные модификации гафдunclassified
“…The ®rst was its inability to discriminate between myristoylated, properly modi®ed recombinant c-Src proteins localized to infected insect cell membranes and unmodi®ed, denatured recombinant c-Src found in both soluble and insoluble states in these cells. Several groups have noted that 50% or more of baculovirusexpressed Src protein is not myristoylated (Gartner et al, 1992;Piwnica-Worms et al, 1990;Ramer et al, 1991). The second drawback is the requirement for using pH 11 bu er to elute c-Src from the column, which inevitably causes some denaturation.…”
Section: Expression and Puri®cation Of C-src From Insect Cellsmentioning
confidence: 99%